AN ANALYSIS OF BUDDHIST PRINCIPLES FOR STRESS MANAGEMENT FOR THE ELDERLY - Phraklupariyattikanchanakich (Suwat Suwattano) (Journal of Contemporary Buddhist Society = JCBS, 2023)
An analytical study of Buddhist principles for stress management for the elderly. The objective was to study the stress problems of the elderly. and to study and analyze Buddhist principles for stress management for the elderly by studying from Tripitaka. Atthakatha. Dika and Pakorn Wiset including Buddhist documents and related research. Stress is a physical and mental state that occurs when demands and obligations outweigh available resources. It can be caused by a number of situations or factors such as work pressure. uncertainty. life changes. worry about the future. and situations that are complex or uncertain. Stress can have physical and mental effects such as headaches. muscle aches. constipation or diarrhea. insomnia. or sleeping too much. and weakened immune function. anxiety. depressed mood. disappointment. feelings of stress. lack of goals. etc. Buddhist principles for stress management for the elderly Principles of Yonisomanasikarn Used to judge stress. by trinity Used to consider the change of stress when it arises and must be extinguished. The three fundamental vices: be aware of the causes of stress caused by lobha. hatred. and delusion. Then use meditation methods to calm that stress. Or should be with a good friend who will advise. advise and persuade in a good way and use the method of prayer so that the mind does not think about various stressful stories. concentrates on single prayers